2001
DOI: 10.1007/bf02680136
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular organization of N2-fixing nodules of cowpea (Vigna unguiculata) supplied with silicon

Abstract: Provision of silicon (0, 0.048, 0.096, 0.24, 0.48, and 0.96 g/l) in the form of silicic acid (H4SiO4) to nodulated cowpea plants (Vignia unguiculata [L.] Walp.) grown in liquid culture resulted in considerable changes in the internal organization of nodule structure. Compared to the control plants which received no added silicate, bacteroid numbers increased significantly (P < or = 0.05) at silicate concentrations of both 0.096 and 0.48 g/l. The number of symbiosomes also increased by 3.2-fold at the silicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In that study, there was a Si-induced increase in the number of bacteroids and symbiosomes in infected cells, which increased N 2 fixation (Nelwamondo et al 2001). So, the higher concentration of Si found in infected cells and in the medulla region of Psoralea nodules in this study (Tables 2, 3 and 4) directly confirms its role in symbiotic functioning.…”
Section: Discussionmentioning
confidence: 91%
“…In that study, there was a Si-induced increase in the number of bacteroids and symbiosomes in infected cells, which increased N 2 fixation (Nelwamondo et al 2001). So, the higher concentration of Si found in infected cells and in the medulla region of Psoralea nodules in this study (Tables 2, 3 and 4) directly confirms its role in symbiotic functioning.…”
Section: Discussionmentioning
confidence: 91%
“…They also found that silicon increased cell wall thickness of root nodules which appeared to decrease intercellular spaces which should, in theory, reduce N 2 fixation because of lower gaseous diffusion (Nelwamondo, Jaffer & Dakora ). The fact that N 2 fixation actually increased led Nelwamondo, Jaffer & Dakora () to speculate that silicification reduced the need for lignin, which is costly in terms of carbon; carbon could then be channelled into bacteroid respiration to increase N 2 fixation. It is also possible that carbon could be channelled towards enhanced nodule organogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…It is also possible that carbon could be channelled towards enhanced nodule organogenesis. Nelwamondo, Jaffer & Dakora () also proposed that silicon supplementation had parallels with phosphorus fertilisation in terms of stimulating root nodulation, including increased production of compounds that up‐regulate nodulation genes (Dakora & Nelwamondo ). This has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…potassium (K), phosphorus (P) and iron (Fe) defi ciency; nitrogen (N), P and boron (B) excess; etc. ]; (17) promotion of nodule formation in legume plants and hence promotion of N 2 fi xation (Nelwamondo and Dakora 1999 ;Nelwamondo et al 2001 ;Mali and Aery 2008 );and (18) promotion of formation of phytolithoccluded carbon and hence having implications in carbon bio-sequestration of atmospheric CO 2 and global climate change (Song et al 2012.…”
Section: Generalmentioning
confidence: 99%